Factors Supporting the Accuracy of External Cause Codes Traffic Accident Injury Cases: Faktor Pendukung Keakuratan Kode External Cause Kasus Cedera Kecelakaan Lalu Lintas - Budiarti, Anggia; Harmanto, Deno; Rahayu, Dinda Sri (Procedia of Engineering and Life Science, 2025)
Injuries due to traffic accidents are one of the third largest causes of death in Indonesia after HIV/AIDS and TB. Based on WHO data (2015), injuries due to traffic accidents are the main cause of death and disability throughout the world, deaths due to traffic accidents worldwide amounted to 1.25 million in 2013. In Indonesia, injuries due to traffic accidents and deaths occurred has become a very serious problem (Djaja et al, 2016). Based on data from the Traffic Accident Unit of the Bengkulu Police Traffic Unit, in 2019 the number of traffic accidents recorded was 33 cases of serious injuries and 173 minor injuries (Munte et al, 2022). Implementation of external cause coding of traffic accident injury cases is very important to be done accurately, because the coding results external cause can be said to be accurate if it has the 4th and 5th characters. If coding is not carried out accurately it will have an impact on disease and action recording index errors, inaccurate report information data and inaccurate INA-CBG rates. all officers provide external cause coding and it is hoped that the head of the medical records unit will make a policy for filling in external cause codes.